Effects of meal type on the oral bioavailability of the ALK inhibitor ceritinib in healthy adult subjects. (24th December 2015) - Lau, Yvonne Y.; Gu, Wen; Lin, Tiffany; Song, Dongweon; Yu, Richard; Scott, Jeffrey W.
Abstract: Ceritinib is a potent inhibitor of anaplastic lymphoma kinase (ALK), which has shown acceptable safety and substantial antitumor activity in ALK‐positive non–small cell lung cancer (NSCLC) patients. Two food‐effect studies were conducted in healthy adults to investigate the influence of food on the oral bioavailability of ceritinib: a study with low‐ or high‐fat meals at 500 mg and a study with a light snack at 750 mg. Compared with the fasted state, AUC0‐∞ (90%CI) of ceritinib was increased by 58% (34%, 86%) after the intake of a low‐fat meal, by 73% (46%, 105%) after the intake of a high‐fat meal, and by 54% (19%, 99%) after the intake of a light snack. Safety assessments also suggested that food may improve gastrointestinal (GI) tolerability after a single ceritinib dose. Based on the pharmacokinetic results, it is essential to avoid any type of meal during dosing of ceritinib because the intake of food may increase the occurrence of exposure‐dependent, non‐GI toxicities at the labeled dose of 750 mg daily during fasting. A randomized trial is ongoing to determine an alternative way to give ceritinib (450 mg or 600 mg with food) that may enhance GI tolerability in ALK‐positive NSCLC patients.